2022
DOI: 10.3390/nano12071154
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Induced Plasmonic Nanobubbles and Microbubbles in Gold Nanorod Colloidal Solution

Abstract: In this work, we studied the initiated plasmonic nanobubbles and the follow-up microbubble in gold nanorod (GNR) colloidal solution induced by a pulsed laser. Owing to the surface plasmon resonance (SPR)-enhanced photothermal effect of GNR, several nanobubbles are initiated at the beginning of illumination and then to trigger the optical breakdown of water at the focal spot of a laser beam. Consequently, microbubble generation is facilitated; the threshold of pulsed laser energy is significantly reduced for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Due to the elevated surface plasmon resonance exhibited by GNPs, the application of high-intensity nanosecond laser pulses induces swift temperature escalation, causing the vaporization of the surrounding medium [21,22]. This process gives rise to the creation of plasmonic nanobubbles (PNBs), or photothermal vapor nanobubbles (PVNBs), along the surface of GNPs [23,24]. The subsequent collapse of these bubbles induces cavitation and stress waves, thereby promoting an efficient heat transfer from the GNPs to the surrounding environment [25].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the elevated surface plasmon resonance exhibited by GNPs, the application of high-intensity nanosecond laser pulses induces swift temperature escalation, causing the vaporization of the surrounding medium [21,22]. This process gives rise to the creation of plasmonic nanobubbles (PNBs), or photothermal vapor nanobubbles (PVNBs), along the surface of GNPs [23,24]. The subsequent collapse of these bubbles induces cavitation and stress waves, thereby promoting an efficient heat transfer from the GNPs to the surrounding environment [25].…”
Section: Introductionmentioning
confidence: 99%
“…The surface-enhanced Raman spectra of CV in AgNP colloids showed that D-AgNP colloids have better SERS enhancement factors than AgNPrs. The eighth paper, authored by S. Y. Yu, C. H. Tu, J. W. Liaw, and M. K. Kuo, studied the initiated plasmonic nanobubbles and the follow-up microbubbles in a gold nanorod (GNR) colloidal solution induced by a pulsed laser [ 8 ]. The advantage of a dilute GNR colloid facilitating laser-induced microbubbles in the NIR range of the bio-optical window could make biomedical applications possible.…”
mentioning
confidence: 99%